2006
DOI: 10.1002/jbm.b.30612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different γ‐irradiation doses on cytotoxicity and material properties of porous polyether‐urethane polymer

Abstract: Biomaterials respond to sterilization methods differently. Steam sterilization might decrease the performance of thermoplastic polyether-urethane (TPU); however, the effect of different gamma-radiation doses on this polymer is contradictory in present literature. The purpose of this study was to investigate the differences between irradiative doses in comparison with steam sterilization on a porous TPU scaffold produced by a new processing method. No significant differences in the surface chemical structure we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 94 publications
1
33
1
1
Order By: Relevance
“…The influence of radiations on the properties and performances of a polymer differs according to the polymer behaviour in terms of degradation or cross linking, and these phenomena are finally dependent on the specific sensitivity of the material to gamma radiations (9)(10). In order to maintain its desirable properties, each polymer presents a fixed maximum dose of irradiation which is mainly dependent on its own chemical structure (11).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of radiations on the properties and performances of a polymer differs according to the polymer behaviour in terms of degradation or cross linking, and these phenomena are finally dependent on the specific sensitivity of the material to gamma radiations (9)(10). In order to maintain its desirable properties, each polymer presents a fixed maximum dose of irradiation which is mainly dependent on its own chemical structure (11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the effect of zeolite content on physical and thermal properties of the polymer was also examined [26,27]. By increasing the silver-zeolite content in the polymer an increased antimicrobial activity was observed (due to the higher silver ion concentration) [22,28] but, depending on the application the zeolite content may influence physical, thermal and/or chemical properties. There are two main reasons to exchange silver as filler in any kind of antimicrobial agent or composite.…”
mentioning
confidence: 99%
“…Gamma irradiation has similar influence on the material. Due to the gamma sterilization, branching on polyurethanes (Haugen et al, 2007) and an extremely high rate of oxidation was observed on UHMWPE implants (Bracco et al, 2006, Goldman et al, 1998. During the irradiation, oxygen penetrates into the amorphous region of the polymer where misfit strain is developed.…”
Section: Fig 5 Sterilization Methods Of Medical Polymersmentioning
confidence: 99%